2017
DOI: 10.3390/f8060181
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Site Suitability as a Combination of Occurrence Probability and Growth and Derivation of Priority Regions for Climate Change Adaptation

Abstract: Two aspects of site suitability were combined, namely species occurrence probability and tree growth as proxies for risk and productivity, aiming to improve climate impact assessments for forests. This measure was used to identify priority regions for climate change adaptation under consideration of current stands. The six most frequent tree species according to German national forest inventory data were used considering repeated measurements. Species distribution and growth models were calculated and combined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…With attention to conifer species such as European larch and Norway spruce, a reduction of habitat suitability is a possible event. A negative variation in habitat suitability of Norway spruce represents a focal point for the high economic value of timber and it reported by different previous works [92,107]. A negative variation in habitat suitability for European larch is also confirmed by Dyderski et al [102] and Mamet et al [108].…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fsupporting
confidence: 63%
“…With attention to conifer species such as European larch and Norway spruce, a reduction of habitat suitability is a possible event. A negative variation in habitat suitability of Norway spruce represents a focal point for the high economic value of timber and it reported by different previous works [92,107]. A negative variation in habitat suitability for European larch is also confirmed by Dyderski et al [102] and Mamet et al [108].…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fsupporting
confidence: 63%
“…With attention to conifers species such as European larch and Norway spruce a reduction of habitat suitability is possible event. A negative variation in habitat suitability of Norway spruce represent a focal point in particular for the high economic value of timber and it reported by different previous works (Hanewinkel et al 2012;Märkel and Dolos 2017;Dyderski et al 2018). A negative variation in habitat suitability for European larch is also con rmed by Dyderski et al (2018) and Mamet et al (2019).…”
Section: Sdm As a Tool For Forest Management Options In The Italian Fsupporting
confidence: 53%
“…Previous studies reveal that oak can occur beyond our covered data range of 633 mm, even with annual precipitation of 450 or 461 mm [74,92]. Märkel and Doloss [111] also showed the highest probability of occurrence at warm temperatures and low-to-medium annual precipitation. Furthermore, dendroecological studies have found a high drought tolerance for oak compared to beech [93,[112][113][114][115].…”
Section: Bioclimatic Suitability Of Beech and Oakmentioning
confidence: 56%